Harmonising international legal frameworks and shariah principles in the context of medical tourism: an analysis - Amin, Noor Shuhadawati; Ramli, Noriah; Zawawi, Majdah (IIUM Press, 2023)
Shariah-compliant medical tourism has grown into a specialised sector of the global medical tourism market that serves patients looking for medical care that complies with Islamic principles. For the sake of ensuring patient safety, ethical considerations, and the harmonisation of practises across borders, the role of international law in governing this special type of medical tourism is essential. The study first establishes a connection between the objectives of the Shariah (Islamic law) together with its salient principles and health in Islam. In this context, it is apparent that the relevant Shariah objectives and principles have a great influence on the delivery of healthcare services. The study, which is doctrinal in nature then explores the international law and how it relates to shariah-compliant medical tourism. Further, the study discusses universal values, human rights, and the protection of patient rights as they are stated in the international conventions. The purpose of this study is to critically analyse the relationship between the Shariah principles in the context of medical tourism with the standards prescribed in the international legal framework. From the study, it is obvious that the international legal standards can accommodate and respect Shariah requirements and has the potential to attract not only Muslims but also non-Muslims patients.